2015
DOI: 10.1007/s10764-015-9844-2
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Diameter and Orientation in the Context of Food Type in the Gray Mouse Lemur, Microcebus murinus: Implications for the Origins of Grasping in Primates

Abstract: Grasping is a widespread behavior among tetrapod vertebrates. In primates, the hands and feet are involved in many tasks including arboreal locomotion and food acquisition. Yet, the origin and the evolution of prehensile capacities, which are highly diversified across this group, remain open for inquiry. Some researchers suggest that grasping evolved in an arboreal habitat consisting of fine branches associated with insect predation and/or fruit and flower exploitation. However, few studies have tested the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 80 publications
1
21
0
Order By: Relevance
“…As the size and shape of the medial tibial facet (MTF) may also indicate habitual inversion of the foot (Boyer et al, ), FHLG position will correlate with MTF size and shape. P3c . Because larger‐bodied euarchontans may more frequently encounter relatively small substrates that require more highly abducted and inverted foot postures (Boyer and Seiffert, ; Dagosto, ; Toussaint, Herrel, Ross, Auard, & Pouydebat, ), there will be a significant relationship between body mass and FHLG position. FHLGs will be more laterally positioned among large‐bodied euarchontans. H4.…”
Section: Introductionmentioning
confidence: 99%
“…As the size and shape of the medial tibial facet (MTF) may also indicate habitual inversion of the foot (Boyer et al, ), FHLG position will correlate with MTF size and shape. P3c . Because larger‐bodied euarchontans may more frequently encounter relatively small substrates that require more highly abducted and inverted foot postures (Boyer and Seiffert, ; Dagosto, ; Toussaint, Herrel, Ross, Auard, & Pouydebat, ), there will be a significant relationship between body mass and FHLG position. FHLGs will be more laterally positioned among large‐bodied euarchontans. H4.…”
Section: Introductionmentioning
confidence: 99%
“…The second hand appears to participate in maintaining balance. Food mobility associated with compliant substrates has also been shown to influence grasping strategies (Nekaris, 2005;Siemers et al, 2007;Scheumann et al, 2011;Toussaint et al, 2013Toussaint et al, , 2015; Peckre L., Lowie A., Wall C., Pouydebat E. & Fabre A-C., unpublished observations). Studies such as this one on captive individuals allow the effect of food properties to be distinguished better from the effects of other environmental variables.…”
Section: Discussionmentioning
confidence: 89%
“…In M. murinus, smaller food items result in more mouth grasps, whereas larger food items lead to enhanced hand use (Reghem et al, 2011). In strepsirrhines, other studies have shown a preference for mouth grasping when grasping static food items and a preference for grasping strategies involving hand(s) when grasping mobile prey (Nekaris, 2005;Siemers et al, 2007;Scheumann et al, 2011;Toussaint et al, 2013Toussaint et al, , 2015Peckre L., Lowie A., Wall C., Pouydebat E. & Fabre A-C., unpublished observations).…”
Section: Introductionmentioning
confidence: 82%
“…Interestingly, in X. laevis mobility induces hand use for small prey. In strepsirrhines it has also been observed that manual grasping increases for mobile prey (Ward and Hopkins, 1993;Reghem et al, 2011;Scheumann et al, 2011;Toussaint et al, 2015). Large prey automatically involve the use of the hands in X. laevis, irrespective of mobility, and involve stretching, laceration and wiping behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we test whether and how food properties modify the use of the hands. As has been described for primates (Pouydebat et al, 2009(Pouydebat et al, , 2014Toussaint et al, 2013Toussaint et al, , 2015, the mobility and the size of a prey item may affect the grasping and manipulation strategies used (e.g. the use of two hands versus one hand, and which fingers are involved in grasping).…”
Section: Introductionmentioning
confidence: 99%